Evaluating food safety risk messages in popular cookbooks. Issue 5 (2nd May 2017) - Levine, Katrina; Chaifetz, Ashley; Chapman, Benjamin
Abstract : Purpose: Medeiros et al. (2001) estimate 3.5 million cases of foodborne illness in the USA annually are associated with inadequate cooking of animal foods or cross-contamination from these foods. Past research shows home food handling practices can be risk factors for foodborne illness. The purpose of this paper is to evaluate the communication of food safety guidance, specifically safe endpoint temperatures and cross-contamination risk reduction practices, in popular cookbook recipes. Design/methodology/approach: Recipes containing raw animal ingredients in 29 popular cookbooks were evaluated through content analysis for messages related to safe endpoint temperature recommendations and reducing cross-contamination risks. Findings: Of 1, 749 recipes meeting study criteria of cooking raw animal ingredients, 1, 497 contained a raw animal that could effectively be measured with a digital thermometer. Only 123 (8.2 percent) of these recipes included an endpoint temperature, of which 89 (72.3 percent) gave a correct temperature. Neutral and positive food safety behavior messages were provided in just 7.2 percent ( n =126) and 5.1 percent ( n =90) of recipes, respectively. When endpoint temperatures were not included, authors often provided subjective and risky recommendations. Research limitations/implications: Further research is needed on the effect of these results on consumer behavior and to develop interventions for writing recipes with better food safety guidance. Practical implications: Including correct food safety guidance in cookbooks may increase the potential of reducing the risk of foodborne illness. Originality/value: Popular cookbooks are an underutilized avenue for communicating safe food handling practices and currently cookbook authors are risk amplifiers.